USING THE METHOD OF «ASSESSMENT» IN TEACHING THE TOPIC OF CARBOHYDRATES - Zaripbayev, K.Sh.; Shurenbaeva, U.; Dzhumanova, Z.K. (My University, 2023)
Different ways to analyze student learning, provide opportunities for testing and self-assessment, and focus on measuring learning and approximate skills. Cognitive activity of students of different directions (testing, teaching problem situations, comparative analysis, symptomatic diagnosis). Improving the long-term plan (target program), which serves for a comprehensive assessment of the knowledge, enterprise and experience of students, determining their capabilities and their development. At the same time, this method (technology) was effectively introduced into the education system. With its help, the level of education, skills and experience of students is comprehensively and fairly assessed.
Keywords: assessment of the level of knowledge; practical skills; creative work; signs; carbohydrates; glucose; sucrose; fructose; starch